A The Relationship Between Bipolar Disorder and Inferiority Complex - Anindyta Risti Pramudya; Fitrania Maghfiroh (International Conference on Psychology and Education (ICPE), 2025)
This researcher examines the case of an adult patient diagnosed with bipolar disorder with major depressive episodes and a history of suicide attempts. The patient exhibits symptoms of an inferiority complex in the form of low self-esteem, feelings of worthlessness, difficulty in making decisions, and social withdrawal. Some of the main triggering factors come from past bullying and unsupportive family relationships. This case analysis uses a clinical psychology approach based on Alfred Adler's individual psychology theory, especially the concept of inferiority complexes. The intervention description focuses on mindfulness techniques and emotional acceptance, so that the patient can build a healthier self-acceptance. This case study emphasizes the importance of family emotional support and appropriate psychological intervention strategies in treating patients with bipolar disorder and an inferiority complex.